International Experience in Assessing Economic Security: Basic Approaches and Opportunities for Ukraine (Law and Safety, 2020)
It has been stated that the implementation of state policy in the field of economic security of the country requires systematic monitoring and adjustment, taking into account the rapid changes in the global world and economic space. This monitoring of the state of economic security of the country should be carried out by obtaining and studying certain factual data that allows to make a conclusion about the effectiveness of joint efforts of the authorized state agencies in the direction of national economic security.The necessity of further study of the effectiveness of the activities of state agencies of foreign countries in the implementation of economic security policy, which would strongly influence the development of the national system for assessing such effectiveness.The author has considered scientific approaches to the definition of the term “economic security” in foreign scientific sources depending on the object of study (country, region, person), as well as indicators of its evaluation.International experience of assessing the economic condition and economic security of foreign countries has been analyzed, which is used both at the level of government and for compiling international ratings of the World Bank and the Bank for Reconstruction and Development. The World Bank and the European Bank for Reconstruction and Development carry out several comprehensive studies of the economic development of the world countries, covering both the assessment of the current state of its main industries and possible security threats arising from the current global tendencies in public life. It is interesting fact in the researched methods that along to purely economic data, experts study related areas, in particular the level of corruption, crime, efficiency of government agencies, the quality of the regulatory base and the level of state intervention in economic processes and business structures. It is also important in these studies that qualitative indicators are used along with quantitative ones, which consist of studying the opinions of the business environment, entrepreneurs and other business entities.The main directions of the implementation of positive international experience in assessing the level of economic security to national practice have been suggested. It has been concluded that the national method of calculating the level of economic security of Ukraine needs to be improved by introducing into its system the indicators of state agencies’ work in the relevant area, defining criteria and indicators for combating economic crime and corruption, improving the mechanism of collecting primary data by adding sociological research, expert assessments and research of foreign financial institutions.
Keywords: economy; economic security; criteria; indicators; evaluation